2015
DOI: 10.1159/000374070
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and/or Estrogen Receptor β Attenuate the Autophagic and Apoptotic Effects Induced by Prolonged Hypoxia Through HIF-1α-Mediated BNIP3 and IGFBP-3 Signaling Blockage

Abstract: Background/Aims: The risk of heart disease is higher in males than in females. However, this advantage of females declines with increasing age, presumably a consequence of decreased estrogen secretion and malfunctioning of the estrogen receptor. We previously demonstrated that 17β-estradiol (E2) prevents cardiomyocyte hypertrophy, autophagy and apoptosis via estrogen receptor α (ERα), but the effects of ERβ on myocardial injury remained elusive. The present paper thus, investigated the cardioprotective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…Instead, there appears to be several mechanisms, and the mechanism likely depends on the cell type and experimental conditions. One model, which fits most data is that upon activation BNIP3L inserts into the mitochondrial outer membrane, and causes opening of the MPTP, loss of ΔΨm, generation of reactive oxygen species, and necrosis [42][43][44][45]. In this study, we focused on the functional significance of the PI3K/AKT/FoxO3a signaling pathway, which was down-regulated in H 2 O 2 -induced cardiomyocyte necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, there appears to be several mechanisms, and the mechanism likely depends on the cell type and experimental conditions. One model, which fits most data is that upon activation BNIP3L inserts into the mitochondrial outer membrane, and causes opening of the MPTP, loss of ΔΨm, generation of reactive oxygen species, and necrosis [42][43][44][45]. In this study, we focused on the functional significance of the PI3K/AKT/FoxO3a signaling pathway, which was down-regulated in H 2 O 2 -induced cardiomyocyte necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating lines of evidence have demonstrated that oxidative stress significantly modulates autophagy during cellular stress [18]. In 2009, Ju Huang found that NOX2 mediated autophagic activity in phagocytes [19].…”
Section: Discussionmentioning
confidence: 99%
“…1A, the red fluorescent dots were gradually increased along with the treatment time of H/R and the eRFP-LC3 dot was obviously more in cells incubated with Rap than those of the control and cells incubated with 3-MA. To further confirm the autophagic activity, the LC3-I (16 kDa) to LC3-II (14 kDa) conversion [20][21][22][23] was checked through western blot analysis. As expected, Rap treatment induced a significant increase of LC3-II/LC3-I ratio in cells as compared with control and cells treated with 3-MA at any duration (P < 0.05; Fig.…”
Section: Effect Of 3-ma and Rap On Autophagy Formation After H/rmentioning
confidence: 99%